Wonder, Wandering, Mystery: Ricoeur on Sexuality and Eroticism – With a Brief Comparison to Marion and Levinas - KEREKES, Erzsébet (Studia Universitatis Babeș-Bolyai Philosophia, 2024)
In this paper, we aim to introduce and analyze a lesser-known text by Paul Ricoeur, “La merveille, l’errance, l’enigme”, which was originally written as an introduction to the November 1960 issue of the journal Esprit, dedicated to the theme of sexuality. Along the two paths of sexuality—tenderness and eroticism—what becomes evident is that sexuality, fundamentally, proves impenetrable to reflection and remains inaccessible to human dominance. After presenting Ricoeur’s reflections on sexuality and eroticism, this paper will also briefly compare his views with those of Jean-Luc Marion and Emmanuel Levinas, highlighting the distinctive contributions of these philosophers in relation to the themes of love, eroticism, and the self-other dynamic.